2012
DOI: 10.1063/1.3680048
|View full text |Cite
|
Sign up to set email alerts
|

Student views of similarity between math and physics problems

Abstract: It is commonly known that students have difficulty connecting the techniques they learn in math classes with necessary steps for solving physics problems. In this study, introductory-level physics students were given a set of pure math problems and a set of physics problems that required them to use the exact same mathematical processes. The students were then asked to pair the analogous problems and explain the pairings. Presented here are the results of that study, which support previous findings that studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The previous research provides an excellent foundation from which to begin a research study encompassing a more holistic view of student use of math in solving physics problems. In previous phases of this project, students were provided a written sample of physics and mathematics problems and were asked to pair the problems according to similarity [11]. Those results showed that students had difficulty with the integrals, as expected from the literature review, and that their difficulties seemed to focus on the difference between definite and indefinite integrals.…”
Section: This Studymentioning
confidence: 95%
“…The previous research provides an excellent foundation from which to begin a research study encompassing a more holistic view of student use of math in solving physics problems. In previous phases of this project, students were provided a written sample of physics and mathematics problems and were asked to pair the problems according to similarity [11]. Those results showed that students had difficulty with the integrals, as expected from the literature review, and that their difficulties seemed to focus on the difference between definite and indefinite integrals.…”
Section: This Studymentioning
confidence: 95%
“…The researchers are therefore investigating in the empirical study why participants' performances on similar tasks in mathematics and physics graphs yielded different responses. There are few investigations on students' application of mathematics knowledge in physics [12,25], whilst most studies focussed on problemsolving (e.g., [5,18]) and specific aspect interpretation like slope of graphs [17,25]. The researchers also found out that less study has been conducted in the four qualitative and quantitative constructs' tasks on the effect of discipline, task and reader characteristics in the mathematics and physics contexts and hence this study.…”
Section: Introductionmentioning
confidence: 99%